The Meaning of Accountability from The Perspective of Sharia Accounting in Bank Muamalat Ambon Managers: A Phenomenological Study - Siti Maryam M. Sillehu; Adnan AS; Buya Rama Ismail; Alimuddin; Darwis Said (Economics and Business Journal (ECBIS), 2026)
This research is motivated by the importance of accountability in Islamic banking, which is not only related to administrative responsibility but also encompasses moral and spiritual dimensions. This study aims to understand the meaning of accountability from a sharia accounting perspective for the managers of Bank Muamalat Ambon. The study used a qualitative approach with a phenomenological method. The study population was the managers of Bank Muamalat Ambon, while informants were selected using a purposive sampling technique based on experience and involvement in Islamic banking activities. The research instrument was a semi-structured interview guide. Data collection techniques were carried out through in-depth interviews and analyzed using phenomenological analysis through the stages of transcription, coding, grouping themes, and extracting essential meanings. The results show that sharia accountability is interpreted as a professional, moral, social, and spiritual responsibility manifested through trustworthiness, transparency, sharia compliance, fair service, and supervision. The conclusion of the study confirms that sharia accountability is not only understood as formal reporting, but as an ethical and religious practice carried out in daily work activities.